FEATURES OF THE ORGANIZATION OF COST ACCOUNTING IN BAKING - E. Sedova; K. Gamazina (Вестник университета)
The article studies specific features of organization of accounting of the cost of bread production. Considered costs by cost center, by types of products, works, services and types of costs, which in turn are divided into expenses according to cost items and costs by cost components.